RESIN MODIFIED GLASS IONOMER CEMENT SEBAGAI MATERIAL ALTERNATIF RESTORASI UNTUK GIGI SULUNG - Diana Setya Ningsih (ODONTO : Dental Journal, 2014)
Glass ionomer cement (GIC) is a material that can release fluoride to prevent caries especially in primary teeth. One of the developments of glass ionomer cement in the world of pediatry dentistry is resin-modified glass ionomer cement (RMGIC). The resin-modified glass ionomer cement were still maintaining the clinical advantages oforiginal material, such as fluoride realease, good compatibility and aestehetically. The mechanical properties of rmgic is more higher than gic. These materials have a better adhesion, higher moisture resistance, and a longer shelft life. This paper review aims to know the ability RMGIC as alternative restorative material for primary teeth.